2011
DOI: 10.1371/journal.pone.0020230
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Bridges in Vertebrate Gastrulation

Abstract: The developing zebrafish embryo has been the subject of many studies of regional patterning, stereotypical cell movements and changes in cell shape. To better study the morphological features of cells during gastrulation, we generated mosaic embryos expressing membrane attached Dendra2 to highlight cellular boundaries. We find that intercellular bridges join a significant fraction of epiblast cells in the zebrafish embryo, reaching several cell diameters in length and spanning across different regions of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 28 publications
4
60
0
2
Order By: Relevance
“…Most of the intercellular bridges were formed at pre-gastrula stages by the daughters of a dividing cell maintaining a membrane tether as they move apart after mitosis. These intercellular bridges persist during gastrulation and mediated the transfer of proteins between distant cells (Caneparo et al, 2011).…”
Section: Embryogenesis and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the intercellular bridges were formed at pre-gastrula stages by the daughters of a dividing cell maintaining a membrane tether as they move apart after mitosis. These intercellular bridges persist during gastrulation and mediated the transfer of proteins between distant cells (Caneparo et al, 2011).…”
Section: Embryogenesis and Developmentmentioning
confidence: 99%
“…They are critical requirement for development, and tissue homeostasis and regeneration. Recent studies have been shown the importance role of TNTs in mechanical and signaling processes during embryonic patterning and development (Caneparo et al, 2011). Interestingly, it have also been reported TNTs can contribute in cellular differentiation and reprogramming by providing a highway to transfer cellular components from one cell to a target cell (Koyanagi et al, 2005;Rolf et al, 2012;Takahashi et al, 2013).…”
Section: Introduction Q2mentioning
confidence: 99%
“…However, the fragility of TNTs and the lack of known molecular markers make it very difficult to observe these structures in their natural environment within tissues. Nevertheless, several studies indicate the presence of TNT-like bridges in vivo during certain developmental processes, such as blastocyst formation and neurulation in mice (Pyrgaki et al, 2010;Salas-Vidal and Lomeli, 2004), dorsal closure in Drosophila (Millard and Martin, 2008) and gastrulation in sea urchin (Miller et al, 1995) and zebrafish (Caneparo et al, 2011). TNTs were also found connecting dendritic cells in mouse cornea (Chinnery et al, 2008) and in other organisms, such as the malaria parasite Plasmodium falciparum (Rupp et al, 2011) and the bacterium Bacillus subtilis (Dubey and Ben-Yehuda, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, these thin, actin-positive cytonemes have been identified in the chick limb bud 16 , where they were suggested to establish Shh signalling gradients over several hundreds of micrometres. Other cell protrusions with the potential to transmit signalling factors were defined as tunnelling nanotubes 17 or intracellular bridges 18 . Whether Wnt molecules can be mobilized on cell protrusions is unclear.…”
mentioning
confidence: 99%